PLAN DE NEGOCIOS PARA LA IMPLEMENTACIÓN DE PRODUCTOS TURÍSTICOS EN LA HACIENDA PUNZARA DE LA CIUDAD DE LOJA - VERA CABRERA, ALEXANDRA DEL CARMEN (2019)
Ecuador is a country with a vast and incomparable natural and cultural wealth, the diversity of its four regions has given rise to the development of thousands of species, which allows the country to have great potential as a tourist destination and can attract more and more tourists. The local tourist activity together with the application of new business projects, is driving towards the development of the localities, taking advantage of each one of the resources that these zones offer. For this reason we propose the theme: Business Plan for the implementation of tourism products in Hacienda Punzara in the city of Loja. For the development of this research project was set a general objective as "Propose a Business Plan for the implementation of tourism products in the Hacienda Punzara in the city of Loja" for which a number of methods and techniques were used. In the same way, three specific objectives were established: "Diagnose the current situation of the Hacienda Punzara in the city of Loja" began with an analysis of the current situation of the farm, using the descriptive method to collect information on internal and external factors to identify alternatives of tourism products that can be implemented in the place. MINTUR tourist attraction sheets were also used to identify and describe each of the hacienda's tourist attractions. In the same way, the interview technique was applied to the people in charge and workers of the hacienda in order to know their expectations related to tourism. In order to know the needs and preferences of the tourists, the survey technique was applied to the local and national tourists of the city of Loja, which resulted in quantitative and qualitative data to be analyzed in order to obtain the tourist products that would be most welcome. With the techniques used previously, it gave way to the creation of a SWOT matrix of the place of study, to be later analyzed and to obtain strategic objectives. In the second specific objective: Business plan for the implementation of tourist products in the Punzara hacienda in the city of Loja. The deductive and analytical methods were applied, which allowed to know the products that are going to be presented and the process that will be carried out for their implementation. 5 For the fulfillment of the third specific objective: To propose strategies for the implementation of the Business Plan of the tourist products of the Hacienda Punzara of the city of Loja. In order to comply with this objective, strategies will be designed to allow the plan to be established and maintained within the market. Therefore, an administrative study was carried out in which the legal and organizational structure of the business can be analyzed, and finally, a financial evaluation was carried out in which it resulted that the initial investment of the project is $66,904 with a Net Present Value of: $213,230 and an Internal Rate of Return of: 95.71%, the capital being recoverable in a year of six months. As a result of the investigation it was concluded that the business plan for tourism products in Hacienda Punzara is viable and profitable, so it is recommended to the owner its implementation as it will improve the quality of life of the locality and tourism development.